(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article examines the features of thinking in children with hearing impairments, which are shaped by the compensatory use of visual, tactile, and practical perception channels. Particular attention is paid to methods of inclusive education, including visualization, practical tasks, and interactive technologies. It has been proven that adapting pedagogical strategies to the specifics of visually-based thinking in such children contributes to the development of their intellectual potential. The article emphasizes the need to integrate an individualized approach and digital tools to enhance spatial perception.